Strategi Pengembangan Wilayah Nodal Pertanian Berdasarkan Klasifikasi Wilayah di Kabupaten Ciamis: Strategy for Developing Agricultural Nodal Areas based on Regional Classification in Ciamis District - Dina Marcelina; Wasrob Nasruddin (Jurnal Agroekoteknologi dan Agribisnis, 2022)
A unit in the region must have different characteristics of involvement in several aspects in order to meet the balance of the region, one of which is the agricultural aspect. Agriculture is an important aspect in the governance of an area because it involves meeting the needs of human life as residents of the area. Sub-districts in Ciamis Regency have different characteristics of involvement in agricultural aspects. This difference lies in the role of each region, namely as a marketing center and a center for agricultural production. The center must be known for the creation of optimal and efficient regional potential development. This study aimed to determine the potential for regional development through the role of the sub-district area using hierarchical analysis. The research method used was secondary data collection techniques sourced from BPS (Central Bureau of Statistics) Ciamis Regency. The results of this regional hierarchical analysis provided data in the form of grouping sub-districts in Ciamis Regency based on the number of infrastructure facilities and population from the big-small ranking system. Region order. This will be the material for determining the location of the center of the role of the nodal region. The result stated that Ciamis District was designated as a marketing center for agricultural products that covers the medium and low hierarchical sub-districts. The regional development strategy was then carried out by strengthening all elements of the agribusiness subsystem.